Rebuilding Communities and Lives: The Role of Damayan and Bayanihan in Disaster Resiliency - Barrameda, Teresita V.; Barrameda, Arlen Sandino V. (Philippine Journal of Social Development; Vol 3 (2011): Philippine Journal of Social Development, 2014)
-